PENGARUH INTERAKSI GENOTIP X LOKASI TANAM TERHADAP KOMPONEN HASIL GALUR POTENSIAL PADI GOGO AROMATIK GENOTYPE X LOCATION INTERACTION EFFECT ON YIELD COMPONENTS OF POTENTIAL PURE LINES AROMATIC UPLAND RICE - D.H., Totok Agung (Pembangunan Pedesaan, 2007)
Crossing between Mentikwangi (aromatic rice variety) and Poso (high yielding upland rice variety) has been conducted. So far, amount of 9 pure of high yielding and aromatic genotypes have been obtained. The objectives of the research were: 1) to evaluate the effect of genotype x location interaction on the yield and yield components of pure lines progeny of crossing between Mentikwangi and Poso, 2) to select pure lines having high yielding across locations, and 3) to select pure lines having high yielding in specific location. An experimental method with randomized completely block design was used in the research. Amount of 13 genotypes (9 pure lines and 4 comparative cultivars) was sown in the field of 8 different locations, namely Cirebon, Purworejo, Tegal, Kebumen, Banyumas, Batang, Kudus, Banjarnegara. The conclusions are as follow. 1. All of the upland rice pure lines perform the good growth and production across 8 different locations. 2. There are genotype x locations interaction on yield components (number of tiller, panicle length, number of grain, and 1000 seed weight) that is showed by changing of the rank of genotypes in different locations. 3. The pure lines which have high yielding across locations are G10 (4,05 t/ha), G19 (4,00 t/ha), G39 (4,18 t/ha), G12 (3.70 t/ha), and G136 (4,10 t/ha). The pure lines having high yielding in a specific location are Situpatenggang (5,40 t/ha) at the fertile locations (Purworejo dan Kebumen).